Transport investment and local and regional development: Perspectives on the emerging motorway system in Poland - Eamonn Judge (European Regional Science Association (ERSA), 1998)
The planned Polish motorway programme is widely expected to have beneficial spinoff effects on local and regional economies within Poland, and on the economy as a whole. Similar arguments were employed during the development of the British interurban road system (and other West European systems). The paper examines the likely relevance and viability of such arguments in the development of the Polish system. The results of current research in the UK are related to the analyses originally employed in the planning and implementation of the Polish network, along with analyses based on more recent data. The topic of the paper has started to assume particular importance in Poland as it becomes more obvious that the projected levels of interurban traffic within and through Poland are likely to be insufficient to finance more than limited sections of the proposed toll motorways. Pressure is building up in Poland for greater governmental support for the network, and possible "non traffic" justifications for construction have begun to assume greater importance. The situation is particularly controversial as environmental lobbies are vocal in opposing motorway developments. The paper will consider the extent to which current research supports, in the Polish context, the employment of such economic development arguments, or whether caution is advisable. The paper is based on work by the author currently in progress at the Department of International Transport of Warsaw School of Economics supported by a PHARE/ACE Research Fellowship.
Keywords: 330